2020
DOI: 10.1016/j.onehlt.2020.100153
|View full text |Cite
|
Sign up to set email alerts
|

The trends of human dirofilariasis in Croatia: Yesterday – Today – Tomorrow

Abstract: Introduction Human dirofilariasis is a disease historically linked to the Mediterranean area. For the last few decades, however, Dirofilaria nematodes have been spreading, both in terms of prevalence and the geographical expansion in non-endemic areas. Currently, cases of human dirofilariasis are recorded in more than 40 countries worldwide. Croatia is considered an endemic area of the Adriatic basin. Methods In a nationwide investigation, new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Other localisations (e.g. pulmonary, oral cavity, eyelid) have also been reported in the literature (9). In Europe, it is recognised as an emergent pathogen.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Other localisations (e.g. pulmonary, oral cavity, eyelid) have also been reported in the literature (9). In Europe, it is recognised as an emergent pathogen.…”
Section: Introductionmentioning
confidence: 86%
“…D. immitis causes a severe cardiopulmonary condition in dogs and other domestic and wild carnivores (5). Although humans are considered as accidental hosts, infections occur occasionally and can cause pulmonary life-threatening conditions and, in some instances, even ocular or subcutaneous diseases (7)(8)(9). D. repens is the agent of subcutaneous diro lariasis in animals and usually has a mild or unrecognised clinical form.…”
Section: Introductionmentioning
confidence: 99%
“…D. immitis may cause a severe cardiopulmonary condition in dogs and other domestic, and wild, carnivores [ 5 ]. Although humans are considered to be accidental hosts, infections occasionally occur and can cause pulmonary conditions and, in some instances, ocular or subcutaneous diseases [ 7 9 ]. D. repens is the agent of subcutaneous dirofilariasis in animals, which usually has a mild clinical manifestation or is unrecognised.…”
Section: Introductionmentioning
confidence: 99%
“…Other localisations (e.g. pulmonary, oral cavity, eyelid) of the disease have also been reported [ 9 ]. In Europe, D. repens is recognised as an emergent pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…D. repens is one of neglected canine lariasis but also found in cats and human (Yilmaz et al, 2016). The epidemiology of D. repens was rstly studied Southern Europe and expanded to Northern Europe (Deksne et al, 2020;Otranto et al, 2013;Pupic-Bakrac et al, 2020). Recently, some study suggested that D. repens in Asia had higher diversity than in European country which purposed name Candidatus D. hongkongensis from Hong Kong and D. repens "Thailand II" found in Narathiwat province, Thailand (To et al, 2012;Yilmaz et al, 2016;Yilmaz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%